Pengaruh Penerapan Pembelajaran Contextual Teaching And Learning (CTL) Pada Bidang Studi Al-Qur’an Hadist Terhadap Motivasi Belajar Siswa Kelas VIII MTs Madinatul Ilmi Lubuk Kertang Kecamatan Brandan Barat - Annisa Salsabilla; Usmaidar Usmaidar; Endah Retno Suci (Yayasan Rahmat Islamiyah, 2022)
The results of the following research findings are based on the results obtained in hypothesis testing and data analysis through the questionnaire that has been given, it is known that the Application of Contextual Teaching and Learning (CTL) Design is good for use in the learning process in schools, especially at MTs madinatul Ilmi. Based on a questionnaire about the use of the application of Contextual Teaching and Learning (CTL) on learning motivation in class VIII students of MTs Madinatul Ilmi, the findings in this study are that there is a positive influence between the application of Contextual Teaching and Learning (CTL) learning on students' learning motivation. The application of Contextual Teaching and Learning (CTL) learning will affect students' learning motivation and vice versa, students' experience abilities have a significant level with the use of the Application of Contextual Teaching and Learning (CTL) Design at MTs Madinatul Ilmi Lubuk Kertang. In this study, it can be seen that Ha is accepted in the sense that there is a significant influence between the application of Contextual Teaching and Learning (CTL) and learning motivation in class VIII Madinatul Ilmi Lubuk kertang students. So it has been obtained Farithmetic: 4.685 and Ftable: (0.5 / 5%) 4.15 it can be concluded that Farithmetic from Ftable is accepted by Ha with the results that there is a significant influence between the Application of Contextual Teaching and Learning (CTL) with learning motivation in class VIII MTs Madinatul Ilmi Lubuk Kertang.